Resistance and integron characterization of Acinetobacter baumannii in a teaching hospital in Chongqing, China - C. Huang; Q. Long; K. Qian; T. Fu; Z. Zhang; P. Liao; J. Xie (New Microbes and New Infections, 2015)
A total of 189 Acinetobacter baumannii isolates were collected in 2011 from a teaching hospital in Chongqing, China. Susceptibility data showed strains carrying integrons were significantly more resistant to all tested antibiotics that strains lacking integrons. Five types of gene cassettes belonging to class I integrons were identified in this study, and for the first time two types of gene cassettes belonging to class II integrons are reported. Most of the cassettes belong to a class I integron (136/144) encoding arr3, aacA4, dfrA17, aadA5, aadB, cat, blaOXA10, aadA1, aadA2, dfrA and aacC1. Isolates contained a class I gene cassette; AadA2-HP-dfrA was the prevalent strain in this hospital. A class II integron was detected in eight strains, which contained the type IV fimbriae expression regulatory gene pilR and sulfate adenylyltransferase, suggesting a possible role in multidrug resistance. The major epidemic strains from intensive care unit patients belong to international clone 2. In conclusion, the presence of integrons was significantly associated with multiple drug resistance of A. baumannii in this hospital, and class I integron isolates bearing AadA2-HP-dfrA were the prevalent strain in this hospital.